Meso-mechanics simulation analysis of microwave-assisted mineral liberation (Fracture and Structural Integrity, 2015)
Microwave-assisted crushing and grinding can improve efficiency and reduce energy consumption. This paper takes rock grains with galena and calcite as the research object to establish a two-dimensional computational model through the finite difference software FLAC2D. It analyzes the process and law of mineral boundary failure under microwave irradiation, and assesses the effects of four factors, namely, microwave irradiation time, power density, mineral crystal size, and mineral content, on mineral boundary failure. Results indicate an optimal microwave irradiation period for the rapid failure of mineral boundary. Moreover, irradiation time and energy consumption can be reduced by increasing the microwave power density. However, irradiation time and energy consumption are basically unchanged when the microwave power density is above a certain threshold. Mineral content slightly affects the microwave irradiation time, whereas mineral crystal size significantly affects the microwave irradiation time. In addition, a larger-sized mineral crystal requires less irradiation time and energy consumption to reach the same failure rate. However, irradiation time and energy consumption slightly change when the crystal size is larger than a certain value.
Keywords: Microwave heating